Estudo do custo de manutenção de estoque em uma empresa de beneficiamento de palmito - SANTOS, Lucas Santos dos (2022)
The study addresses the Inventory Management, which today is a very relevant issue for companies seeking effective alternatives to continue highlighting the global and competitive scenario. Sought to parti bibliographic research, the approach of theory with practice, to carry out within the organization's environment an objective analysis of how it deals with and manages its storage of raw materials. It also presents a brief description of the analyzed organization as well as its production process. Regarding the practical approach, we sought with the case study, applying a model of inventory, based on data provided by the company, which is compatible with the reality of it. So is research, enables the operation of this activity in the company, highlighting the importance of relevant information to inventory control, contributing to greater efficiency of the production process, and thus reduce the costs caused by poor management of stock.